2010
DOI: 10.1111/j.1469-8137.2010.03431.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of foliar manganese (Mn) in Mn (hyper)accumulators using X‐ray absorption spectroscopy

Abstract: Summary Plant hyperaccumulation of the essential nutrient manganese (Mn) is a rare phenomenon most evident in the Western Pacific region, and differs from hyperaccumulation of other elements. Mn hyperaccumulators employ a variety of species‐dependent spatial distribution patterns in sequestering excess foliar Mn, including primary sequestration in both nonphotosynthetic and photosynthetic tissues. This investigation employed synchrotron X‐ray absorption spectroscopy (XAS) in a comparative study of Mn (hyper)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
71
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 72 publications
6
71
0
Order By: Relevance
“…The Mn in roots of the four species was mostly Mn(II) complexed by malate or citrate. This finding and that of LC-MS analysis is in keeping with that of Fernando et al (2010), who concluded that malate or citrate is the most likely carboxylate to complex Mn in hyperaccumulators. Dou et al (2009), however, determined oxalate to be important, a finding not supported by data for the species examined in this study.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The Mn in roots of the four species was mostly Mn(II) complexed by malate or citrate. This finding and that of LC-MS analysis is in keeping with that of Fernando et al (2010), who concluded that malate or citrate is the most likely carboxylate to complex Mn in hyperaccumulators. Dou et al (2009), however, determined oxalate to be important, a finding not supported by data for the species examined in this study.…”
Section: Discussionsupporting
confidence: 75%
“…A similar mechanism would occur in white lupin also (data not shown). Using XANES, Fernando et al (2010) concluded that Mn(II) predominates in Mn hyperaccumulators, with Fernando et al (2008) being the first to show that Mn is evenly distributed in leaf photosynthetic and nonphotosynthetic tissues. White lupin would be classified as a Mn accumulator (van der Ent et al, 2013) by growing well at 100 mM Mn, with leaves containing 17.1 and 25.0 mmol Mn kg -1 FM (14,100 and 20,700 mg Mn kg -1 DM; Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…detoxification are suggested through analysis of foliar Mn species in Mn hyperaccumulator plants (Xu et al, 2009;Fernando et al, 2010). Furthermore, increased organic acid exudation from roots was observed in ryegrass (Lolium perenne) and white clover (Trifolium repens) subjected to different Mn levels (Rosas et al, 2007;de la Luz Mora et al, 2009), suggesting that secreted organic acids might be responsive to Mn toxicity.…”
mentioning
confidence: 99%